Development of Bioplastic Films from Cassava Peel Starch Reinforced with Banana Midrib Nanocellulose and the Effect of Sorbitol on Mechanical Strength - Anita Maharani Albarkah; Betty Marita Soebrata; Tetty Kemala (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
Cassava peel and banana midrib, two abundant agricultural wastes, were utilized as sources of starch and cellulose to develop environmentally friendly bioplastic films. Cellulose was isolated through delignification and bleaching, followed by ultrasonication to produce nanocellulose. The obtained nanocellulose was characterized using Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), and a Particle Size Analyzer (PSA), which confirmed distinct cellulose functional groups, a crystallinity index of 58.7%, and an average particle size of 326.44 nm. Bioplastic films were prepared by blending cassava peel starch with banana midrib nanocellulose and varying concentrations of sorbitol as a plasticizer. The incorporation of nanocellulose increased thickness, density, and tensile strength, while reducing water absorption and water vapor transmission rate (WVTR), likely due to the reinforcing effect of nanocellulose within the polymer matrix. The addition of sorbitol at different concentrations influenced the mechanical properties of the bioplastics, with the composition containing 0.89 g sorbitol exhibiting favorable tensile strength and elongation. The optimal formulation consisted of 2.85 g cassava peel starch, 0.15 g nanocellulose, and 0.89 g sorbitol, yielding a tensile strength of 2.76 MPa and an elongation of 11.19%. These findings demonstrate that incorporating sorbitol and nanocellulose significantly enhances the performance of starch-based bioplastics, highlighting their potential application in sustainable packaging materials.